Northern geometrid forest pests (Lepidoptera: Geometridae) hatch at lower temperatures than their southern conspecifics: Implications of climate change - Fält-Nardmann, Julia; Klemola, Tero; Roth, Mechthild; Ruohomäki, Kai; Saikkonen, Kari (European Journal of Entomology)
Climate change may facilitate shifts in the ranges and the spread of insect pests, but a warming climate may also affect herbivorous insects adversely if it disrupts the locally adapted synchrony between the phenology of insects and that of their host plant. The ability of a pest species to colonize new areas depends on its ability to adjust the timing of phenological events in its life cycle, particularly at high latitudes where there is marked seasonality in temperature and day length. Here we incubated eggs of three species of geometrid moth, Epirrita autumnata, Operophtera brumata and Erannis defoliaria from different geographical populations (E. autumnata and O. brumata from Northern Finland, E. autumnata and E. defoliaria from Southern Finland and all three species from Germany) in a climate chamber at a constant temperature to determine the relative importance of geographic origin in the timing of egg hatch measured in terms of cumulative temperature sums (degree days above 5°C, DD5); i.e. the relative importance of local adaptation versus phenotypic plasticity in the timing of egg hatch. In all three species, eggs from northern populations required a significantly lower temperature sum for hatching than eggs from southern populations, but the differences between them in temperature sum requirements varied considerably among species, with the differences being largest for the earliest hatching and northernmost species, E. autumnata, and smallest for the southern, late-hatching E. defoliaria. In addition, the difference in hatch timing between the E. autumnata eggs from Southern Finland and Germany was many times greater than the difference between the two Finnish populations of E. autumnata, despite the fact that the geographical distances between these populations is similar. We discuss how these differences in hatching time may be explained by the differences in hatch-budburst synchrony and its importance for different moth species and populations. We also briefly reflect on the significance of ...